Silk Suture Granuloma 37 Years After Scleral Buckle Surgery: A Case Report. Issue 10 (October 2021) - Zein, Mike; Theotoka, Despoina; Wall, Sarah; Galor, Anat; Cabot, Florence; Patel, Umangi; Dubovy, Sander; Karp, Carol L.
Abstract : Purpose: To present a rare presentation of pyogenic granuloma arising almost 4 decades after a scleral buckle for retinal detachment. Method: We describe the clinical presentation, diagnostic workup, and management of a suspicious conjunctival lesion in an immunocompromised patient. We report the histopathological findings and the postoperative outcome. Results: A 58-year-old man with human immunodeficiency virus presented for evaluation of a possible malignant conjunctival lesion in the left eye. The patient reported that the lesion had appeared 1.5 months before presentation with significant growth over the past month. The patient denied any trauma to the eye other than an ocular history of retinal detachment repair with scleral buckle 37 years earlier. Clinical examination revealed a pink, fleshy, mobile, and lobulated conjunctival lesion measuring 7 mm by 10 mm, emanating from the superior–nasal bulbar quadrant. A high-resolution optical coherence tomography revealed highly cellular infiltrate and hyperreflective mass with significant posterior shadowing. Further exploration of the lesion revealed a white, stringy, cauliflower-like material on the underside of the lesion. Surgical excision and pathology subsequently confirmed a diagnosis of pyogenic granuloma with remnants of silk suture. Conclusions: A diagnosis of pyogenic granuloma secondary to retained silk sutures should be considered in patients with a history of intraocular surgery irrespective of other risk factors and length of time since procedure.